Urban Planning And Urbanization Processes In The Khorezm Oasis - Davletov Sanjar Rajabovich; Allanazarov Sirojbek Bekchan ugli (International Journal on Human-Computing Studies, 2021)
This article deals with the processes of urbanization of the cities of the Khorezm oasis,their construction and architectural methods. The article also provides an analysis of the literature on the subject